Integration of the Concept of Human Life Purpose in the Formulation of Islamic Education - Qomusuddin, Ivan Fanani; Latifah, Siti; Sam'un, Sam'un; Basri, Hasan (CV RIFAINSTITUT, 2025)
Islamic education has an important role in shaping human life goals in accordance with monotheistic values. The integration of the concept of human life goals in the formulation of Islamic education aims to create an educational system that not only focuses on academic aspects, but also shapes the character and spirituality of students. This research uses a qualitative method with a library research approach, which examines various literature, journals, and references related to Islamic education and the concept of human life goals from an Islamic perspective. In addition, this study also analyzes the principles of Islamic education in shaping human life goals and how to integrate these concepts in the Islamic education curriculum. The results of the study show that the ideal Islamic education must combine religious and general science, apply learning methods based on spiritual reflection, and create a conducive educational environment. The role of educators, families, and the government is crucial in supporting the implementation of this concept. With the right integration, Islamic education can produce a generation that is knowledgeable, moral, and has an awareness of their life goals according to Islamic teachings. Therefore, synergy between various parties is needed to realize Islamic education that is able to form individuals who contribute to Islamic society and civilization